2013
DOI: 10.1111/1753-6405.12118
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of a mentoring program for Aboriginal health workers and allied health professionals

Abstract: Conclusions: Peer mentoring betweenAboriginal and non-Aboriginal health workforce was found to be a powerful mechanism to promote two-way learning that has the capacity to meet learning needs and promote practice improvement.Implications: Peer mentoring may be part of a multi-strategy approach to the development of the Aboriginal health workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 11 publications
2
47
0
1
Order By: Relevance
“…Through critical reflection encouraged by Aboriginal people and dietetic supervisors, graduates in the present study reported being able to deepen their cultural understanding in a broader attempt to make sense of their altered worldview. This notion is supported by previous research that has explored the role of both Aboriginal mentors and non‐Aboriginal mentors that are experienced in cross‐cultural situations, in developing a health professional’s cultural competence . In addition, study results suggest that by learning how to build trust and respect with Aboriginal people through observation of role models in Aboriginal health, dietetic graduates may be better equipped to develop positive relationships with Aboriginal people and have increased confidence to work in the field.…”
Section: Discussionsupporting
confidence: 76%
“…Through critical reflection encouraged by Aboriginal people and dietetic supervisors, graduates in the present study reported being able to deepen their cultural understanding in a broader attempt to make sense of their altered worldview. This notion is supported by previous research that has explored the role of both Aboriginal mentors and non‐Aboriginal mentors that are experienced in cross‐cultural situations, in developing a health professional’s cultural competence . In addition, study results suggest that by learning how to build trust and respect with Aboriginal people through observation of role models in Aboriginal health, dietetic graduates may be better equipped to develop positive relationships with Aboriginal people and have increased confidence to work in the field.…”
Section: Discussionsupporting
confidence: 76%
“…[7][8][9][21][22][23][24] It was also found that the existing workforce distribution is uneven, 21,22 the nonAboriginal workforce is aging, 8,23 Aboriginal people make up a small proportion of the health workforce and face significant challenges entering and staying in the health workforce 12,17,24 and the cultural competence of the existing health workforce is variable. 25,26 The primary strategies identified to address these issues are to promote rural and remote Aboriginal health practice to students; provide additional support, such as training, improved cultural competence, and peer mentoring to the existing health workforce; and develop and support the Aboriginal health workforce at a local level.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12]27 At the same time, Aboriginal people in the health workforce are likely to have a positive effect on the patient experience of the healthcare service, which may, in turn, improve trust, attendance at appointments and acceptance of assessment and treatment recommendations. 11,18,[24][25][26]28 All nine papers identified the importance of the Aboriginal health workforce and the need to provide specific support, such as education, training, mentoring, cultural and family leave provisions, as well as peer support, to address the significant issues they face. Equally important are explicit strategies for acknowledging, preventing and dealing with racism; strategies to promote team cohesion and cooperation; recognition and respect of different knowledge (e.g.…”
Section: Experience Of the Aboriginal Health Workforcementioning
confidence: 99%
“…It is therefore important that a workforce development strategy is identified that can support dietitians to work in Aboriginal health, enable them to develop their skills and retain working in the area. Mentoring models have shown some potential in the area of Aboriginal nutrition, including peer mentoring partnerships between Aboriginal health workers and dietitians sharing cultural, community and nutrition expertise . However, currently, there is a lack of evidence about how to best support dietitians working in the Aboriginal health sector …”
Section: Introductionmentioning
confidence: 99%